Wakalah bi al-Ujrah in Letter of Credit Services: Sharia Bank Applications - Liswardi, Liswardi (Journal of Economicate Studies, 2024)
This study analyzes the application of the Wakalah bi al-Ujrah contract in Letter of Credit (LC) services within Sharia banks. As an agency-based contract, Wakalah bi al-Ujrah enables banks to act on behalf of clients in facilitating trade transactions while charging a transparent service fee. This paper adopts a qualitative literature-based approach, reviewing books, journal articles, and institutional guidelines. Findings indicate that the contract ensures Sharia compliance, strengthens customer trust, and provides operational efficiency in trade finance. Nevertheless, challenges persist, including limited customer literacy, regulatory inconsistencies, and misinterpretation of fee structures. To optimize implementation, strategies such as enhancing Sharia governance, improving transparency, and expanding educational initiatives are recommended. The study contributes theoretically by integrating agency and risk management perspectives in Islamic finance and practically by providing insights for regulators and practitioners to enhance competitiveness in global trade facilitation